The Degree to which Early Childhood Teachers Possess the Competencies of Employing Blended Learning at Public Schools in the State of Qatar from their Point of View - Al-Mohsen, Noor; Qadhi, Saba; El Rous, Adel Abo (Dirasat: Educational Sciences, 2022)
Objectives: The current study aims to determine the degree to which early childhood teachers possess the competencies of employing blended learning at public schools in the State of Qatar from their point of view. Methods: The study used a blended learning competency framework. The questionnaire consisted of (34) items distributed to (267) early childhood teachers. Results: The study found that the childhood teachers possess the competencies of employing blended learning in all fields at high rates in general and in varying proportions according to the adequacy of the way of thinking, qualitative sufficiency, adaptive skills, and technical skills. Conclusions: In the light of the results of the study, the researchers recommend continuing to develop the competencies of early childhood teachers towards employing learning theoretically and practically.